The association between estradiol levels and cognitive function in postmenopausal women - Soheila Gholizadeh; Shahideh Jahanian Sadatmahalleh; Saeideh Ziaei (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Levels of estradiol decreases as women arrive the menopausal transition and enter to a low, steady level during the early postmenopause. In addition, memory dysfunction are highly prevalent during this period. Objective: Our study was designed to determine whether endogenous levels of estradiol are related to cognitive function in postmenopausal. Materials and Methods: The cross-sectional study was conducted between November 2015 to February 2016 on 209 healthy postmenopausal women. The women filled out the Montreal Cognitive Assessment (MoCA) scale. Then, estradiol level was tested for association with cognitive function adjusted for factors supposed to confound this association. Results: The prevalence of cognitive dysfunction; MoCA points ≤26 in our participants was 62.7%, and mean±SD of estradiol level was 14.92±10.24pg/ml in participants with cognitive dysfunction in comparison with 21.67±14.92pg/ml in those with normal cognitive function (p<0.001). There were significant association between MoCA points with estradiol level (p<0.001) and educational status (p<0.001). Conclusion: Estradiol replacement therapy in postmenopausal women with low endogenous estradiol levels and decreased cognitive function might be necessary.